Ictiofauna de la pesquería ribereña en Bahía de Navidad, Jalisco, México, asociada al evento El Niño 1997-1998 - J.A. Rojo-Vázquez; B. Aguilar-Palomino; V.H. Galván-Piña; E. Godínez-Domínguez; S. Hernández-Vázquez; S. Ruiz-Ramírez; G Lucano-Ramírez (Revista de Biología Tropical, 2001)
Se cuantificó la ictiofauna obtenida por la pesquería ribereña de Bahía de Navidad, Jalisco, México durante 1998. Se capturaron 6 944 ejemplares distribuidos en 130 especies (3 231 kg). Las familias con mayor número de especies fueron Carangidae, Haemulidae y Sciaenidae. Las especies más importantes en número y biomasa fueron Microlepidotus brevipinnins, Caranx caninus, C. caballus. El máximo número de especies se registró en junio (61), mínimo en marzo (33). En enero se capturó la mayor abundancia (1397 organismos), la menor durante agosto (25). La mayor biomasa fue en enero (556.5 kg), y la menor en agosto (114.7 kg). Dieciocho especies acumularon el 86.7 % de la abundancia total, mientras que 20 especies reúnen el 86.3 % de la biomasa. De igual forma, se encontraron grandes diferencias entre el número de especies, la abundancia y la biomasa capturados en los diferentes tipos de redes The ichthyofauna fished in Bahía de Navidad. Jalisco, Mexico in the Central Pacific was surveyed during 1998. Six thousand nine hundred and fourty-four organisms of 130 species were caught which weighted P. 231 kg. Nearly 30 % of the species belonged to Carangidae, Haemulidae and Sciaenidae. The most important species in number and biomass were Microlepidotus brevipinnins, Caranx caninus and C. caballuso Species number, abundance and biomass fluctuated during the year. The largest number of species was caught in June (61), the minimum in March (33). January had the maximum abundance (1 397 organisms), while the minimum was obtained during August (251). The maximum biomass values were from January (556.5 kg), and the lowest from August (114.7 kg). Eighteen species accumulated 87 % of the total abundance. while 20 species represented 186.3 % of the biomass. There were large in differences species number, abundance and biomass nets of differ lent mesh size